Motility, Viability, Spermatozoa Abnormality, and pH of Bali Cattle Semen in Another-Yellow Water Driller Stored in a Different Time - Fransiskus X. Manehat; Agustinus Agung Dethan; Paulus Klau Tahuk (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2021)
This study aims to determine the quality of Bali cattle spermatozoa diluted using sugarcane juice-egg yolk. This research was carried out in the stables and Laboratory of the Faculty of Agriculture, University of Timor in August-September 2020. Semen was collected from an adult male bali cattle, aged ± 4.5 years in healthy condition. The method used in this study is an experimental method using a completely randomized design consisting of 4 treatments and 5 replications. Each treatment was T1: 0.075 ml semen + 0.3 ml of egg yolk sugarcane juice diluent and stored for 24 hours, T2: semen 0.075 ml + 0.3 ml of diluent for egg yolk cane juice and stored for 48 hours, T3: semen 0.075 ml + 0.3 ml of diluent for egg yolk sugarcane juice and stored for 72 hours, T4: semen 0.075 ml + 0 ,3 ml of egg yolk sugarcane juice diluent and stored for 96 hours. The variables measured were individual motility, viability, spermatozoa abnormalities, and semen pH. The results showed that the T4 treatment on a shelf life of 96 hours still showed a good average value with individual spermatozoa motility values of 45%, spermatozoa viability of 77.3%, spermatozoa abnormalities of 12.5% and semen pH 6.6. It can be concluded that the use of cane juice-egg yolk diluent has a positive impact because it is able to maintain the viability of spermatozoa for 96 hours.